Surveillance for Guillain-Barré syndrome after 2015–2016 and 2016–2017 influenza vaccination of Medicare beneficiaries. Issue 43 (8th October 2019) - Arya, Deepa P.; Said, Maria A.; Izurieta, Hector S.; Perez-Vilar, Silvia; Zinderman, Craig; Wernecke, Michael; Alexander, Michael; White, Taylor; Su, I-Hsuan; Lufkin, Bradley; MaCurdy, Thomas; Kelman, Jeffrey; et al.
Highlights: No influenza vaccine had excess Guillain-Barré syndrome (GBS) risk 1–42 days post-vaccination. All seasonal influenza vaccines had GBS risk within expected range, 8–21 days post-vaccination. The high dose influenza vaccine had GBS risk within expected range, 8–21 days post-vaccination. Standard dose influenza vaccines had no excess GBS risk 8–21 days post-vaccination. Difference in GBS risk after different vaccine types is hypothesis-generating. Abstract: Background: Guillain-Barré syndrome (GBS) is a serious acute demyelinating disease, an increased risk of which was found after the 1976 swine flu vaccinations. The U.S. Food and Drug Administration, in collaboration with the Centers for Medicare & Medicaid Services, has been conducting active surveillance for GBS after influenza vaccinations of Medicare Fee-For-Service beneficiaries since 2009. Methods: We conducted active surveillance for GBS claims in the 2015–2016 and 2016–2017 influenza seasons using the Updating Sequential Probability Ratio Test (USPRT) to monitor for signals of GBS risk. We performed self-controlled risk interval (SCRI) analyses at the end of both seasons, including chart confirmation in the 2015–2016 season, to estimate the odds ratio of GBS risk. We used 1–42 and 8–21 days post-vaccination as primary and secondary risk windows, respectively, and 43–84 days post-vaccination as the control window. Results: Over 13 million beneficiaries were vaccinated in each season. USPRT found a low magnitude signal for GBS in both seasons. SCRI analyses did not find excess GBS risk following any influenza vaccine for days 1–42 post-vaccination in either season. In the 2015–2016 season, for the 8–21 day window, our chart-confirmation showed an attributable GBS risk of 0.87 (95% CI: 0.16, 1.49) and 1.68 (95% CI: 0.69, 2.41) cases per million vaccinees after all seasonal and high dose (HD) vaccines, respectively, an elevated GBS risk for beneficiaries aged ≥75 years following all seasonal vaccines (OR: 2.25; 95% CI: 1.15, 4.39) and HD vaccine (OR: 3.67, 95% CI: 1.52, 8.85), and an elevated GBS risk for males who received seasonal vaccines (OR: 2.18; 95% CI: 1.15, 4.15) and HD vaccine (OR: 3.33; 95% CI: 1.35, 8.20). The finding of elevated GBS risk with advancing age and in males is consistent with literature; however, a distinction between HD and SD was a new finding. In the 2016–17 season, for the 8–21 day window, attributed cases showed an attributable GBS risk of 0.87 (95% CI: 0.03, 1.61) and 1.11 (95% CI: 0.00, 2.01) cases per million vaccinees after all seasonal and HD vaccines, respectively. We found no excess GBS risk for standard dose vaccines in the 8–21 day window in either season. Conclusions: Our primary analysis finding of no excess GBS risk during both seasons was reassuring. The slightly elevated GBS risk, although in the expected range, in the 8–21 day window after all seasonal and high dose vaccines, but not after standard dose vaccines is hypothesis-generating because the difference may be due to vaccine factors such as antigen amount or strains in various seasons or due to host factors.